Analisis Maslahat terhadap Digitalisasi Program Selalu Samawa dalam Pencatatan Perkawinan di KUA Padang Panjang Barat - Melany Putri; Fajrul Wadi (Lembaga Yasin AlSys, 2026)
The digitalization of marriage administration services has received attention in various studies, but research that specifically analyzes the benefits of the digitalization of the SELALU SAMAWA Program in marriage registration at the Office of Religious Affairs (KUA) of West Padang Panjang remains limited. This study aims to analyze the implementation of the digitalization of the SELALU SAMAWA Program in marriage registration and examine it from the perspective of maslahat in Islamic law. This study employed a qualitative approach with a field research and qualitative descriptive design. The research participants included officers of the KUA of West Padang Panjang, officers of the Population and Civil Registration Office (Disdukcapil), and bridal couples who participated in the SELALU SAMAWA Program, who were selected through purposive sampling. Data were collected through observation, interviews, and documentation and were then analyzed descriptively and inductively through the stages of data reduction, data presentation, and conclusion drawing. The results showed that the digitalization of the SELALU SAMAWA Program improved the effectiveness of marriage administration services through system integration between the KUA and Disdukcapil, enabling the public to obtain post-marriage administrative documents more quickly, practically, and efficiently. This program also contains elements of maslahat because it facilitates services, protects the administrative rights of the public, and supports orderly marriage registration from the perspective of maqashid al-syari’ah. Nevertheless, the program’s implementation still faces obstacles in the form of network disruptions, delays in data synchronization, and limited digital literacy among the public. The conclusion of this study affirms that the digitalization of the SELALU SAMAWA Program plays an important role in strengthening the effectiveness, accessibility, and public benefit of marriage administration services. These findings provide a theoretical contribution to the development of studies on maslahat in the digital transformation of public services and a practical contribution to strengthening digital-based marriage administration systems within the KUA environment.